The complete nucleotide sequence of the genomic RNA of bean common mosaic virus strain NL4 - Bravo, E; Calvert, Lee A.; Morales, Francisco José (2008)
The complete nucleotide sequence of the genomic RNA of the NL4 strain of Bean common mosaic virus (BCMV-NL4) was determined. The viral genome is 10037 nucleotides in length, excluding the 3 terminal poly (A) tail, and contains a single open reading frame (ORF) of 9666 nucleotides encoding a polyprotein of 3222 amino acids. . The ORF is flanked by 5 and 3 untranslated regions (UTRs) of 133 and 235 nucleotides, respectively. Comparative analyses of the predicted BCMV-NL4 polyprotein with other species of the genus Potyvirus revealed nine cleavage sites resulting in ten functional proteins. Nucleotide and amino acid sequence identities indicated a close relationship between BCMV- NL4 and BCMV-NL1. Blast comparisons using coat protein (CP) and 3 UTR sequences showed 100% identity between BCMV-NL4 and the Mexican variant (US6) of this strain.